Household Production of Cookies from Sorghum (Sorghum bicolor) with a Low Glycaemic Index in Prevention and Management of Type 2 Diabetes in Côte d’Ivoire - Camara, Fatoumata; Coulibaly, Wahauwouele Hermann; Sakia Mian, Tano Marie-Ange; Ahoussi, Koua Jean-Brice; Coulibaly, Salimata; Varadarajan, Vijayakumar; Diguta, Camelia; Matei, Florentina (Bentham Science Publishers Ltd., 2025)
Background: In Côte d’Ivoire, sorghum was most commonly used to produce beer. However, the population must focus on other sorghum uses. Sorghum possesses numerous health and nutritional benefits that must be explored, such as its involvement in diabetes management and prevention. Globally, the prevalence of diabetes is rising. Understanding the glycemic index (GI) is crucial for managing and preventing it. The GI gauges how quickly or slowly blood glucose rises in response to a meal. Objective: The aim of this study was to investigate the glycemic index (GI) of sorghum household cookies. Methods: The macro- and micronutrients and phytochemical compounds content of sorghum cookies have been determined. Microbiological analysis of sorghum cookies during storage at room temperature has been carried out by spoilage germ and pathogenic germ enumeration. The glycaemic index (GI) of sorghum cookies has been investigated by the blood sugar response method. Results: In this study, the results showed that the sorghum-based biscuit has an energy value of 515.655 ± 0.5 Kcal/GMS due to its carbohydrate content of 54.95 ± 0.028%, fat content of 30.05 ± 0.05%, and protein content of 6.34 ± 0.0141%. It also contains minerals such as sodium (3.21 ± 0.014 mg), phosphorus (14 ± 0.41 g), and calcium (122 ± 5.65 mg). The phenolic compound content was: total phenols 2756.72 ± 294.5 μg EAG/gMS, flavonoids 497.29 ± 13.016 μg EQ/gMS, and condensed tannins 651.59 ± 199.429 μg EC/gMS. The glycaemic index of household cookies made from sorghum was investigated. The results revealed that sorghum cookies exhibited a low glycaemic index of 40.82%, which is less than 55% in accordance with the norm. Also, microbiological analysis showed the total absence of spoilage germs and pathogenic germs during 30 days of storage at room temperature. Conclusion: Sorghum cookies present a low glycaemic index and can be used in diabetes management and prevention. They are stored at room temperature for 30 days under hygienic conditions.